Kecakapan Berbahasa Anak melalui Program Pembelajaran Bilingual Kelompok B di RA Masjid Al-Akbar Surabaya - Anisa Dewi Maulidiya; Ilun Muallifah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
In the era of globalization, language proficiency in early childhood is crucial for supporting their cognitive and social development. At RA Masjid Al Akbar Surabaya, a bilingual program (Indonesian-English) is implemented for Group B to optimize children's language skills. This study aims to analyze the impact of the bilingual program on children's speaking, listening, and language comprehension aspects. The research method used is descriptive qualitative, with data collection techniques through observation, interviews with teachers and parents, and documentation. The subjects of the study are children in Group B who participate in the bilingual program. The results show a positive impact of the bilingual program on children's language development. Children are able to interact actively in both languages, both in speaking and listening, and show improvements in language comprehension. This bilingual program has proven effective in enhancing children's communication skills and supporting holistic language development from an early age. Therefore, the bilingual program at RA Masjid Al Akbar can be used as a model for developing language skills in early childhood to prepare them for the challenges of globalization in the future.